Transversal competencies in augmented reality-based history learning - Karima, Elfa Michellia; Wulandari, Fikhen Tri; Firza, Firza; Abianza, Erza (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
This research is based on the weak ability of students to implement historical learning assessments due to the lack of supporting competencies. This study aims to analyze the use of transversal competencies to achieve learning objectives in learning planning in historical learning assessment courses. This study used experimental methods to analyze data. The result of the research is that transversal competencies applied in learning and delivering material in the history learning assessment course are more meaningful and more accessible to implement coupled with the history learning assessment course, which is a practical course. The application of transversal competencies in the learning planning of history learning assessment courses in History Department students will also emphasize specific skills, knowledge, values, and attitudes necessary for effective participation in supporting the student learning process.